SELECTIVITY OF HERBICIDES APPLIED SEPARATELY OR IN COMBINATION IN THE POST EMERGENCE OF RR2 MAIZE - Giovanelli, Bruno Flaibam; Silva, André Felipe Moreira; Albrecht, Alfredo Junior Paiola; Aiello, Luiz Henrique Freguglia; Ghirardello, Giovani Apolari; Albrecht, Leandro Paiola; Victoria Filho, Ricardo (REVISTA DE AGRICULTURA, 2018)
The goal was to evaluate the tolerance of maize hybrids 2B810 PW and 30F35 HR to herbicides applied alone and in combination. Trials were carried out in the field in a randomized block design with four replicates. The treatments were three herbicides, alone or in combination, in addition to the control. Herbicides were: atrazine (2000 g ai ha-1); nicosulfuron (50 g ai ha-1) and glyphosate (1080 g ae ha-1). Crop injury was evaluated at 7, 14, 21, and 28 days after application and also SPAD index, height, ear height, stem diameter, 1000-grain weight, and yield. In general, the variables were not affected by the treatments. Hybrids 2B810 PW and 30F35 HR showed tolerance to the application in post-emergence (V4) of the herbicides used.